Selection of structure and parameters of pneumatic impact unit with built-in tank - Атаманов, Юрий Леонидович; Крутиков, Геннадий Анатолиевич; Стрижак, Марьяна Георгиевна (Technology audit and production reserves, 2014)
The problems of selecting the structure of a pneumatic impact unit and its parameters are considered in the paper. The results of the PC testing (personal computer) of the pneumatic actuator activation process with various wiring schemes of actuating mechanism are given. The analytical dependences and diagrams for selecting the parameters of the pneumatic impact unit, allowing the improvement of the compressed air efficiency and ensuring the maximum impact velocity on the workpiece without changing the weight and size characteristics of the impact cylinder, are proposed. Based on the PC research, it was determined that a pneumatic scheme with cylinder and air distribution operation synchronization allows achieving the most efficient pulse impact at which it is possible to avoid the cylinder head impact, as well as improving the energy characteristics of the pneumatic unit. All research results are presented in a dimensionless form. Such representation makes them universal and allows for extending it to a group of similar pneumatic units.